Kajian Etnobotani Tumbuhan Jombang di Desa Sukamanah Kecamatan Pangalengan, Jawa Barat - Silmi Aulia Putri; Tri Cahyanto (Institut Nalanda, 2024)
Ethnobotany has a domain of study on the relationship between humans and plants, including the role of humans in understanding their interactions with the environment around their place of residence. Sukamanah Village is located in a beautiful area and is still very close to nature. Jombang plants are very easy to find because they are classified as wild plants. This study aims to determine the utilization of Jombang plants as traditional medicine in Sukamanah Village, Pangalengan District. Knowledge about the use of Jombang plants is obtained from generation to generation. The method used was interviews with descriptive and quantitative data analysis. The purpose of the study was to determine the utilization of Jombang plants. Jombang leaves are utilized by boiling and then the boiled water is consumed as a medicinal plant 81.25% for the stomach and 18.75% for the flu. 62.5% of them boiled the Jombang leaves directly, 25% dried the leaves first before boiling, and the last 12.5% boiled the leaves and roots. The use value (UV) of this plant is very low because the utilization known by the interviewees is small.